PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PERSONAL SELLING TERHADAP KEPUASAN PELANGGAN UNTUK MENINGKATKAN MINAT PEMBELIAN BERULANG DI SAPPHIRE RESTAURANT EL HOTEL ROYALE JAKARTA - Rezha Dio Saputra Sanjaya; Surono (Human Capital Development, 2023)
The objective of this research is to identify the influence of product quality, price perception, and personal selling on customer satisfaction to enhance repeat purchase intentions at Sapphire Restaurant in EL Hotel Royale Jakarta. The population for this study comprises customers who have visited and made purchases at Sapphire Restaurant in EL Hotel Royale Jakarta. The sampling technique used is purposive sampling, resulting in a total of 118 respondents. This research utilizes a quantitative method.The findings of this study indicate that product quality does not have a significant impact on customer satisfaction, price perception does not have a significant impact on customer satisfaction, but personal selling has a positive influence on customer satisfaction. Moreover, customer satisfaction has a significant impact on repeat purchase intentions.